Police perceptions of restorative justice: Findings from a small‐scale study. (28th August 2018) - Gavin, Paul; MacVean, Allyson
Abstract : This paper considers the views and perceptions of police officers and staff from a local police force in England, on the training provided in, and use of, restorative justice. These views were obtained through the use of an online questionnaire as well as the recording of comments made by police officers and staff after one training session. While the overall sample is too small to draw any concrete conclusions, participants appeared to share views expressed in similar, larger studies. This study adds to the literature on restorative justice as police views in this area are underresearched in England and Wales.